Natural and Digital Landscapes in the Actions of Kollektivnye Dejstvija - Roberta Sala (RiCognizioni)
The present article examines the aesthetic evolution of liminal spaces in the actions of the Moscow Conceptualist group Kollektivnye Dejstvija (Collective Actions), analysing them as material semiotic borders between different communicative domains. The initial Soviet phase of the group began in 1976, while in 1989 the collective broke up. In 1995, some of its members reunited under the name [KD], and they have remained active since then. The aim of the group is to understand the nature of art beyond any socio-political conditioning. Each of the actions involves the staging of a minimalist performance, attended by a group of selected spectators-participants; most of these events are enacted outdoors, with the Kievogorskoe pole—an untilled field on the outskirts of Moscow bordered by woods—representing the main setting in the Soviet phase. Since 1980, the group’s actions have been archived through the samizdat project Poezdki za gorod (Trips out of Town), of which fifteen volumes have been produced to date.